Synthesis and EPR studies of the first water-soluble N@C60 derivative. Issue 95 (8th November 2017) - Cornes, Stuart P.; Zhou, Shen; Porfyrakis, Kyriakos
Abstract : We report a water-soluble N@C60 derivative and investigate its use as a spin probe for Cu(ii ) ions. Abstract : The first water-soluble derivative of the paramagnetic endohedral fullerene N@C60 has been prepared through the covalent attachment of a single addend containing two permethylated β-cyclodextrin units to the surface of the carbon cage. The line width of the derivative's EPR signal is highly sensitive to both the nature of the solvent and the presence of Cu(ii ) ions in solution.